Impact of Psychosocial Risk Factors in Post-Pandemic Times in a Colombian University Institution - Panesso Patiño, Vanessa; Calderón Puerta, Sandra Marcela; Claribel Núñez, Nadia (Journal of Organizational Psychology, 2023)
The study presented is the evaluation of psychosocial risk factors in The Antonio José Camacho University Institution in the city of Santiago de Cali, Colombia, where every 1 or 2 years the survey of psychosocial risk factors is applied where intra-work and extra-work factors of workers are measured, it is applied to teachers and administrative staff. The survey defined from the survey of psychosocial risk factors of the Colombian Ministry of Health and Social Protection applied to teachers (103) is used and the results are extracted quantitatively and qualitatively. According to the results, the Antonio José Camacho University Institution still shows a satisfactory range of 75%, decreasing the percentages in comparison with the 2021 period. Where this decrease is most observed is in the demands corresponding to the intra-work factors. The Institution must continue with these measurements that lead to know the post-pandemic effects on workers. University institutions are called to further assess psychosocial risk factors in their organizations due to post-pandemic effects and draw intervention plans for their workers to have a healthy lifestyle.